O futuro da política Brasileira: uma comunicação para jovens eleitores - Druck, Chiara Einloft (2021)
The lack of interest of young people in Brazilian politics becomes a problem as they are a considerable part of the decision-making power. In this way, the present work has the general objective of disseminating knowledge about the functioning of the policy for young people from 15 to 17 years of age in the city of Passo Fundo / RS and region. In order to achieve the same, primary data surveys were carried out through interviews with the target audience and as a close audience and secondary data collection through bibliographic research. For the success of the objective, the planning of the campaign was made based on primary quantitative data as a target audience that, thus, collaborated for the development and creation of the campaign, tactics and strategies of public interest about Brazilian politics. , contributing to the diffusion of knowledge.